Розроблення схеми екологічної мережі Немирівського району Вінницької області - Іщенко, В.А.; Коріненко, М.С.; Кватернюк, С.М. (Екологічна безпека та природокористування, 2012)
On the basis of environmental studies and analysis of protected are asselectedkey, binders, buffer and recoveryareas that form the basisof the developes chemesecological net work Nemirovsky District, which is part o a regional ecological net work Vinnytsia region.